Creating An Alternative Design for Asita Corporate Identity - Michelle Elise; Vera Jenny Basiroen (Humaniora, 2015)
The objective of the study is to find the solution to the problem outlined, which is to create an alternative design for corporate identity of ASITA. ASITA is a non-profit organization to foster tours and travel agencies in Indonesia. The writer conducted interview to the ASITA Jakarta Chapter, which was appointed to represent ASITA in providing the data needed by the writer. The writer interviewed the advisor of the organization, which had once served as chairperson of ASITA. The result of the research is new corporate identity system of ASITA based on a concept that ASITA as an organization, serves as a compass that guides and assists in every direction. The writer found that corporate identity is an important element to define an organization as well as giving impact on its first impression. To create good corporate identity, several things such as elements of design, color, typography, etc need to be put into attention.